Turtle Beach Hotel, Tobago -F28 - Yhap, Christine (CPPP Ltd., 2010)
The postcard shows the Turtle Beach Hotel, one of the larger hotels located on the island of Tobago.
Colour: Coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Postcards; Hotels; Beaches; Trinidad and Tobago